EFEKTIVITAS PERMAINAN KARUTA TERHADAP KEMAMPUAN MENGINGAT KOSAKATA BAHASA JEPANG (Penelitian Eksperimen Murni terhadap Siswa Kelas X SMA Pasundan 8 Bandung) - Mudrikah, Dela Diah (2017)
PenelitianinibertujuanuntukmengetahuiefektivitaspermainanKarutaterhadapkemampuan　mengingatdalampenggunaankosakatabahasaJepang. Penelitianinimerupakanpenelitiankuantitatif model eksperimenmenggunakandesainPretest-Postest Control Group Design yang diaplikasikanpadapesertadidik SMA Pasundan 8 Bandung TahunAjaran 2016/2017. Teknikpengumpulan data dilakukandenganmemberikan pre-test kepadaduakelompokyaitukelaseksperimendankelaskontrol, kemudiandiberiperlakuan (treatment) menggunakanpermainanKarutapadakelompokeksperimendanmenggunakan media power point padakelompokkontrol, yang selanjutnyadiberikan post-test danangket.Hasil data penelitiandiolahmenggunakananalisisstatistik. Nilai rata-rata pre-test padakelompokeksperimenadalah 41,5dankelaskontroladalah 39,75, sedangkannilai rata-rata post-test kelompokeksperimenadalah 89,75, dankelompokkontrol 81,75. Ditinjaudarinilai gain (normalized gain) kelompokeskperimenmengalamipeningkatansebesar 0,82, sedangkankelompokkontrolsebesar 0,69. Berdasarkan hasil penelitian menunjukan bahwa permainan Karuta efektif dalam meningkatkan kemampuan siswa dalam mengingat kosakata dasar bahasa Jepang. Kata Kunci Efektivitas, Permainan,Karuta, KemampuanMengingat, KosakataBahasaJepang;--- This study aims to determine the effectiveness of Karuta game to the ability to remember in Japanese Vocabulary learning. This research is an quantitative research by model experimental study conducted for Pretest-Postest Control Group Design at students of High school Pasundan 8 Bandung Academic Year 2016/2017. The method used for collecting data by providing the pre-test to two groups as experiment class and control class, then treated (treatment) by applying Karuta game in experiment class, and used power point in contol class, the final stage by giving the post test and questionnaire. The result of research used statistical analysis. With an average value of pre-test scored 41,50 in experiment class and 39,75 for control class, while average value of post-test scored 89,75 in experiment class and 81,75 for control class. The results of the normalized gain, students of experiment class obtained a score improvement 0,82, and students of control class score obtained 0,69. Based on the results of the study showed that application of Karuta game can improve the effectiveness of the ability to remember in Japanese Vocabulay learning. Keywords :Effectiveness, Karuta, Game, The ability to remember, Japanese Vocabulary;--- 本研究の目的は日本語の単語学習における暗記能力を向上するためのカルタゲームの活用の効果を明らかにするための研究である。本研究は使用された方法はクオンツ分析である。研究のデザインはPretest-Postest Control Group Designを使用した。それで対象者は2016/2017年度パスンダン8バンドン高等学校の一年生である。データを収集するために使用された方法は実験教室と管制教室にプレテストを行った。実験教室でカルタゲームの活用の実験を行った。また一方で、管制教室でパワーポイントの活用の実験を行った。両教室の対象したにポストテストとアンケートを答えてもらった。研究の結果は統計的分析を使用した。プレテストの平均点は実験教室で41,50点で,管制教室で39,75点を得た。また一方で、ポストテストの平均点は、実験教室で89,75点で、管制教室で81,75点を得た。Normalized gainの結果によって、実験教室の向上スコアは0,82点であり、管制教室の向上スコアは0,69点の結果であった。この結果を見ると、カルタゲームは日本語の単語の暗記能力を向上させるために効果があると分かった。 キーワード　：使用、カルタ、ゲーム、暗記能力を向上、日本語の単語